Issue of Moral Degradation Among Muslim Adolescents in Malaysia: Issues, Challenges and Suggested Solutions - Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Syh Noorul Madihah Syed Husin; Mohamad Aniq Aiman Alias; Nurul Syazwani Abdullah Kahar; Lukman Abdul Mutalib; Nik Salida Suhaila Nik Saleh; Zulfaqar Mamat (Usuli Faqih Research Centre PLT., 2024)
Indexed by MYCITE